A Bibliometric Analysis of Hybrid Maize Research using VOSviewer - Taufiq Hidayatullah; Irfan Suliansyah; Etti Swasti; Nurwanita Ekasari Putri (Jurnal Biologi Tropis, 2023)
Corn (Zea mays L.) is one of the most widely cultivated commodities in the world after rice. This study aims to (1) evaluate the most effective database available at Harzing's Publish or Perish software with a year-range search method and the use of additional keywords to obtain the highest number of manuscripts from journal sources relevant to maize hybrids in the field of plant science and agriculture and (2) assess the publication of articles and types of reviews on hybrid maize research related to plant science and agricultural by mapping and visualizing of bibliometric analysis. The data of bibliometric analysis was collected from PubMed, Google Scholar, Semantic Scholar, and CrossRef in Harzing's Publish or Perish software. The keyword used in this research was "hybrid maize" with the year of publication of the article 1962-2021. CrossRef  has the highest number of total relevant manuscripts compared to the others. The search method for years is the most effective and efficient if the number of manuscripts is less than 1000. The topic of hybrid maize was mainly published in 2020. The journal that published the most on maize hybrid was Crop Science, especially from 1982- 2011. VOSviewer keyword analysis found that there were 5 clusters from 122 items, 1851 links, and total link strength of 5516. The topic of hybrid maize has been massively published since 2010. Apart from that, hybrid maize and gene were also the two most discussed topics.